Selected aspects of the tourist space of the Lublin Region (case study) - Świeca, Andrzej; Brzezińska-Wójcik, Teresa; Jóźwik, Marta Jolanta; Krukowska, Renata; Skowronek, Ewa; Tucki, Andrzej (Turyzm/Tourism, 2014)
The article presents the results of studies on the tourist space of the Lublin Region conducted so far by employees of the Department of Regional Geography and Tourism at the Faculty of Earth Sciences and Spatial Management of the Maria Curie-Skłodowska University. The studies, regarding the environmental and cultural tourist values, the level of management and transport accessibility, as well as selected elements of the tourism policy of the local authorities, permitted the determination of the tourist potential of spatial units (administrative and physicogeographical) with various importance and character. Areas with varied degrees of attractiveness were distinguished based on their tourist potential. Those classified as attractive and very attractive were described in detail in terms of: the degree of development of the tourist function, functional types of spatial units, perception of tourist space by users, and attitudes of the local community towards the development of tourism.